Diseño de un proceso de selección de personal basado en competencias conductuales para el puesto de atención e información al usuario de asista centros médicos: Quito, 2021 - García Goitía, María Bethania (2021)
The purpose of this research project is to design a competency-based selection process for the Customer Service position at Asista Centros Médicos. The focus of this research is based on studies by Hay Group and Spencer & Spencer that suggest that competencies can offer a competitive advantage to organizations through a decrease in staff turnover and in the overall increase of productivity of employees, among other things. For this reason, in order to achieve the selection process, the competency profile of the position was designed through three fundamental instruments, established in the Hay Group methodology: the 360º competency questionnaire, the behavioral event interview and the expert’s panel. This, in order to create a focused behavioral event interview, based on the competencies obtained, and include it in the selection process as the fundamental tool for the selection of candidates. Similarly, indicators have been defined to evaluate whether the proposed process achieves the desired impact. The modality used for this project is field and documentary, and the methods used are inductive - deductive and analytical - synthetic. The result obtained from the research project is the selection process based on competencies, which is proposed as the solution to the problem of job adaptation found in the area of Customer Service at Asista Centros Médicos.